Electrochemical Removal of Rare Earth Element in LiCl-KCl Molten Salt. (10th August 2020) - Kim, Gha-Young; Jang, Junhyuk; Paek, Seungwoo; Lee, Sung-Jai
Abstract : This study was carried out to examine the removal of rare earth (RE) elements by electrodeposition for the purification and reuse of LiCl-KCl salt after electrorefining and electrowinning. The electrochemical behavior of RE elements (Dy and Gd) in LiCl-KCl-DyCl3 -GdCl3 at 500°C was investigated using the cyclic voltammetry (CV) technique using Mo and Mg electrodes. It was observed that the reduction potential of the RE elements shifted at the Mg electrode owing to the alloy formation with Mg (RE-Mg alloy). Subsequently, a series of potentiostatic electrolysis tests were conducted to remove the RE elements in the salt and check the formation of deposits at the Mg and Mo electrodes. The scanning electron microscopy-energy dispersive X-ray spectroscopy (SEM/EDS) technique was used to confirm that the reduced RE metals were deposited on the surface of the Mg electrode. However, no significant deposit on the Mo electrode was observed, and a mud-like deposit was found on the bottom of the electrochemical cell. The salt analysis performed by employing the inductively coupled plasma-optical emission spectrometry (ICP-OES) indicated that the removal efficiency of Dy 3+ and Gd 3+ through electrodeposition was 83.5∼95.2 and 91.6∼95.2%, respectively.